Elevated Galectin-3 levels in the tumor microenvironment of ovarian cancer – implication of ROS mediated suppression of NK cell antitumor response via tumor-associated neutrophils - Karlsson, Veronika; Stål, Ebba; Stoopendahl, Emma; Ivarsson, Anton; Leffler, Hakon; Lycke, Maria; Sundqvist, Martina; Sundfeldt, Karin; Christenson, Karin; Bernson, Elin (Frontiers in Immunology, 2024)
IntroductionOvarian cancer is a lethal disease with low survival rates for women diagnosed in advanced stages. Current cancer immunotherapies are not efficient in ovarian cancer, and there is therefore a significant need for novel treatment options. The β-galactoside-binding lectin, Galectin-3, is involved in different immune processes and has been associated with poor outcome in various cancer diagnoses. Here, we investigated how Galectin-3 affects the interaction between natural killer (NK) cells and neutrophils in the tumor microenvironment of ovarian cancer.MethodAscites from the metastatic tumor microenvironment and cyst fluid from the primary tumor site were collected from patients with high-grade serous carcinoma (HGSC) together with peripheral blood samples. Galectin-3 concentration was measured in ascites, cyst fluid and serum or plasma. Neutrophils isolated from HGSC ascites and autologous blood were analyzed to evaluate priming status and production of reactive oxygen species. In vitro co-culture assays with NK cells, neutrophils and K562 target cells (cancer cell line) were conducted to evaluate NK cell viability, degranulation and cytotoxicity.ResultsHigh levels of Galectin-3 were observed in cyst fluid and ascites from patients with HGSC. Neutrophils present in HGSC ascites showed signs of priming; however, the priming status varied greatly among the patient samples. Galectin-3 induced production of reactive oxygen species in ascites neutrophils, but only from a fraction of the patient samples, which is in line with the heterogenous priming status of the ascites neutrophils. In co-cultures with NK cells and K562 target cells, we observed that Galectin-3-induced production of reactive oxygen species in neutrophils resulted in decreased NK cell viability and lowered anti-tumor responses.ConclusionTaken together, our results demonstrate high levels of Galectin-3 in the tumormicroenvironment of HGSC. High levels of Galectin-3 may induce production of reactiveoxygen species in ascites neutrophils in some patients. In turn, reactive oxygen species produced by neutrophils may modulate the NK cell anti-tumor immunity. Together, this study suggests further investigation to evaluate if a Galectin-3-targeting therapy may be used in ovarian cancer.